2017
DOI: 10.1080/15384101.2017.1325045
|View full text |Cite
|
Sign up to set email alerts
|

Daam1 regulates fascin for actin assembly in mouse oocyte meiosis

Abstract: As a formin protein, Daam1 (Dishevelled-associated activator of morphogenesis 1) is reported to regulate series of cell processes like endocytosis, cell morphology and migration via its effects on actin assembly in mitosis. However, whether Daam1 plays roles in female meiosis remains uncertain. In this study, we investigated the expression and functions of Daam1 during mouse oocyte meiosis. Our results indicated that Daam1 localized at the cortex of oocytes, which was similar with actin filaments. After Daam1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 41 publications
(44 reference statements)
0
15
0
Order By: Relevance
“…This structure, the actin cortex, contributes to morphogenesis of interphase cells, and drives cell rounding during cytokinesis ( Bray and White, 1988 ; Chugh and Paluch, 2018 ). In human cells, the assembly of actin cortex depends on both formins and the Arp2/3 complex ( Bovellan et al, 2014 ; Lu et al, 2017 ; Cao et al, 2020 ). Ezrin, radixin, moesin (ERM)-family proteins link the cortical actin meshwork to the plasma membrane in interphase cells and during mitosis ( Bretscher et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…This structure, the actin cortex, contributes to morphogenesis of interphase cells, and drives cell rounding during cytokinesis ( Bray and White, 1988 ; Chugh and Paluch, 2018 ). In human cells, the assembly of actin cortex depends on both formins and the Arp2/3 complex ( Bovellan et al, 2014 ; Lu et al, 2017 ; Cao et al, 2020 ). Ezrin, radixin, moesin (ERM)-family proteins link the cortical actin meshwork to the plasma membrane in interphase cells and during mitosis ( Bretscher et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mass spectrometry combined with a visual screen has shown that in melanoma M2 cells, the cortex is nucleated predominantly by the formin mDia1 (encoded by DIAPH1 ) and the Arp2/3 complex ( Bovellan et al, 2014 ). In mouse oocytes, the formin Daam1 also contributes to cortex assembly ( Lu et al, 2017 ). Interestingly, in HeLa cells, mDia1, but not Arp2/3, is essential for cell division ( Bovellan et al, 2014 ), and in Drosophila notum cells, cortical actin nucleation shifts from being dominated by Arp2/3 to formin upon mitosis entry ( Rosa et al, 2015 ).…”
Section: Cortex Compositionmentioning
confidence: 99%
“…These processes are mediated by actin binding proteins including F-actin nucleators, regulators of actin assembly and disassembly, and actin crosslinkers (28, 32). F-actin nucleators include formins which nucleates and lengthens the linear F-actin (33), and the actin-related protein 2/3 (ARP2/3) complex which promotes the formation of branched F-actin (28, 34). The nucleators are important in regulating cortical elasticity and cortex tension through controlling the length of actin filaments, which allows cells to adapt to environments with different mechanical properties (30, 35).…”
Section: Structure Of the Cortical Actin Cytoskeletonmentioning
confidence: 99%